Interface Pharmacotechniques: Conditions and Opportunities - K. A. Ocheretyany (Дискурс)
Introduction. The article deals with finding environmental patterns for the digital environment – at the moment, digital environments are more likely to bring a person closer to machine and technical requirements. The article poses a question (and a detailed answer is given) about how and under what conditions technology does not absorb a person, but gives her the opportunity to reveal her potential, turning it into existential capital.Methodology and sources. Methodologically, the work is based on philosophical analytical research and precedents of the digital field, examples of research literature, methods of media philosophy, anarchic epistemology, and topological reflection are applied. In particular, the hypotheses of the digital space as simultaneously communicative and disciplinary (Habermas, Foucault) digital behaviorism by B. Fogg, the economics of forgiveness by D. Graeber, the anthropology of the game by R. Caillois, Internet animals by A. Pscher were analyzed: on their basis, the principles of digital ethology and ecology.Results and discussion. The task of converting interfaces into ecological and pharmacological environments is the task of organizing by means of interfaces of various types of agencies. They should be organized in such a way that the modes of energy consumption and operation are replaced by modes of energy saving and care. In this case, the interfaces of digital devices could be not a continuation of the technical bureaucracy, but the conditions for comprehending and collecting the experience of the world. The project for this reorganization of funds – from exploitation to pharmacology – was proposed in the article. The article shows that the interface of digital devices can be not only a tool (techne) or a form of vision and cognition of the world (episteme), but also an ecological life-saving environment (pharmacy) for this it is necessary to take into account a number of factors: 1) counter-standardization and counter-personalization of the interface – it must to collide not with oneself, but with another, in all the radicalism of one’s otherness; 2) the ability to move from meaning to presence, and focus not on the consumption of ideological texts as standardized scenarios, but on the creation of contexts of existential interaction; 3) rejection of the agonality of digital consumption (which leads to emotional burnout) in favor of recognizing the uniqueness and incommensurability of experience, and, accordingly, creating conditions for mutual recognition and mutual trust, which are the main capital of a modern person in an era of semantic impenetrability in digital, the growth of suspicion and cynicism.Conclusion. The interface turns from a disciplinary space into a field of care when it becomes possible by means of the interface to go beyond itself, when it grants the right to postponement, to inattention, to offline, when instead of a tool of intensifying life, it becomes a condition for its deeper living. To do this, one should turn from techniques of drawing attention in the interface to techniques of organizing and interpreting the experience of the world.